2015
DOI: 10.3906/sag-1309-64
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of hemostasis-related parameters for prediction of organ dysfunction and mortality in sepsis

Abstract: Background/aim: Clinical manifestations of sepsis are not caused directly by the invading pathogens, but rather mostly by systemic inflammation that leads to activation of the coagulation system. The aim of this study was to determine whether levels of hemostasisrelated parameters measured in intensive care unit admissions are associated with mortality and severity in patients with sepsis.Materials and methods: Eighty-five patients who fulfilled criteria for a diagnosis of sepsis were included in our study. Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 18 publications
(30 reference statements)
3
17
0
1
Order By: Relevance
“…54 Additionally, prolonged aPTT has been correlated with a worse prognosis in both humans and dogs with systemic inflammation or sepsis. 55,56 Initial radiographic findings were consistent with previously reported findings in dogs with BP. 2,3 The resolution of the alveolar lung pattern was followed during hospitalization and follow-up visits.…”
Section: Discussionsupporting
confidence: 85%
“…54 Additionally, prolonged aPTT has been correlated with a worse prognosis in both humans and dogs with systemic inflammation or sepsis. 55,56 Initial radiographic findings were consistent with previously reported findings in dogs with BP. 2,3 The resolution of the alveolar lung pattern was followed during hospitalization and follow-up visits.…”
Section: Discussionsupporting
confidence: 85%
“…Platelet count is a well-known indicator of the severity of systemic infections. [26] However, data regarding the diagnostic value of PLT for acute appendicitis remains limited. Two recent studies that each included fewer than 260 patients similarly found that PLT had no diagnostic value for acute appendicitis.…”
Section: (E)mentioning
confidence: 99%
“…We have previously studied patients with severe sepsis or septic shock and demonstrated that both APTT and PT‐INR on admission to the ICU correlate with mortality . In another study on septic patients, it was shown that patients with increased PT‐INR and D‐dimer and prolonged APTT developed more severe organ failure . Several studies have been performed on trauma patients, and the findings indicate that low levels of fibrinogen and high levels of fibrin degradation products (FDP), D‐dimer and PT‐INR, are associated with increased mortality .…”
Section: Introductionmentioning
confidence: 99%
“…7 In another study on septic patients, it was shown that patients with increased PT-INR and D-dimer and prolonged APTT developed more severe organ failure. 8 Several studies have been performed on trauma patients, and the findings indicate that low levels of fibrinogen and high levels of fibrin degradation products (FDP), D-dimer and PT-INR, are associated with increased mortality. [9][10][11][12][13] In an unselected general ICU population in China researchers investigated the correlation between mortality and PLC, APTT, PT-INR, D-dimer, fibrinogen and FDP at admission to the ICU.…”
Section: Introductionmentioning
confidence: 99%